Demosthenica - Hernández Muñoz, Felipe G. (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2006)
We present four studies on the text of Demosthenes, containing: (1) critical notes on the speeches 19-24; (2) a research into the sources of the Aldine(s) editions; (3) a study on the Lexica demosthenica preserved in the manuscript Complutensis 30; and (4) the «mén-dé law for the authenticity of Demosthenes’ work».